Information and communication technology and the role of information in terms of the radical modernization of society (Pedagogy of Higher and Secondary Education, 2016)
Drohaytsev A. I. Information and communication technology and the role of information in terms of the radical modernization of society.This article focuses on the role of information in modern society.Nowadays, there is a need for a qualitatively new teacher training, which would combine the fundamental nature of the professional knowledge and innovative thinking and practical oriented, research approach to the resolution of specific teaching and educational issues.Ukrainian National Doctrine of Education Development in the 21st century provides a gradual transition from a reproductive, authoritarian education to education of an innovative, humanistic type. It provides mainly training of the future specialist, who would be able to acquire high-quality knowledge. According to these facts, the problem of information competence formation is kept up to date in different spheres of life.Information transition from the sphere of social consciousness to self-consciousness is caused by internal factors, the most important of which are the professional orientation and self-concept of the future specialist. Under these conditions, the general and individual comparison occurs in the position of self-actualization and self-sufficiency of the individual that shows its pragmatic approach to information.Increasing the amount of information is particularly noticeable in the field of education. First of all, it is realized in the creation of new educational courses and communication technologies (A. Korinnyi), computerization of education, deremination of professional prospects of activity (A. Sukhanov), the transformation of the spiritual heritage, and the development of culture (H. Vorobiev). An updated education ceases to be only a pedagogical process and acquires the characteristics of the information process.Under the informatization of society, the process of formation of students’ specific competencies, abilities of receiving quality knowledge from modern information sources acquires unconditional value. A student must learn how to choose professionally important knowledge from diversity, offered by modern information space. The way to receive information is the availability of skills to learn independently and to obtain information. Therefore our attention is focused on the formation of the information competence and the role of information under the radical modernization of society in this article.
Keywords: information; information and communication technologies; computerization; information culture; modernization of society; field of information; education; formation of information